Espaço, territórios e doenças vetoriais : ensinamentos dos países do Sul para lutar contra a ameaça das arboviroses no Brasil? - Pascal Handschumacher; Florence Fournet; Walter Ramalho (Confins)
Vector-borne diseases are a constantly renewed threat to human health. Vectors adaptation, climate change, environment modifications, globalization, urbanization, promote the persistence or even the emergence and diffusion of these infectious risks. In Brazil, today’s preoccupations are focused on Aedes transmitted arboviruses. The country is facing the rise of dengue, Zika, Chikungunya and the persistence of yellow fever. Other vector-borne diseases such as schistosomiasis, persist around the irrigated perimeters of Sao Francisco River. The spatial dynamics of these diseases underline the role of the structuring of spaces, the functioning of networks, the growth of urbanization, and the supply of care, echoing studies carried out around vector-borne diseases, in other places and on other continents. By recalling the geographical teachings resulting from some interdisciplinary work examples, we propose to renew the focus on vector-borne diseases by confronting experiences on both sides of the Atlantic, or even then South American borders.